1998
DOI: 10.1038/sj.bjc.6690055
|View full text |Cite
|
Sign up to set email alerts
|

Allelotype influence at glutathione S-transferase M1 locus on breast cancer susceptibility

Abstract: SummaryThe influence of polymorphisms of the glutathione S-transferase gene GSTM1 in breast cancer susceptibility has been assessed in this study. Previous studies correlated the absence of the GSTM1 protein with an increased risk of developing some cancers, especially lung or bladder cancers, in heavy smokers. In this study, we determined GSTM1 polymorphisms in a population of 437 female controls from the west of France and 361 community breast cancer patients. Three distinct alleles of this gene exist: GSTM1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
2
4

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 30 publications
0
20
2
4
Order By: Relevance
“…Although previous studies observed a significant interaction between GSTM1-null, GSTT1-null genotypes and alcohol consumption in the risk for breast cancer among premenopausal women (Park et al, 2000) and among both pre-and postmenopausal women (Helzlsouser et al, 1998), the potential association between individual GSTM1 alleles and breast cancer or their interaction with alcohol consumption in modifying the risk of breast cancer was not investigated. Our findings in this study are, however, consistent with those in several reports indicating potential differences in the effects of GSTM1A and GSTM1B in breast and other cancers (Fryer et al, 1993a, b;Duncan et al, 1995;Inskip et al, 1995;Charrier et al, 1999). There is also the possibility that GSTM1 may be linked to another gene involved in the metabolism of putative breast carcinogens.…”
Section: Discussioncontrasting
confidence: 46%
“…Although previous studies observed a significant interaction between GSTM1-null, GSTT1-null genotypes and alcohol consumption in the risk for breast cancer among premenopausal women (Park et al, 2000) and among both pre-and postmenopausal women (Helzlsouser et al, 1998), the potential association between individual GSTM1 alleles and breast cancer or their interaction with alcohol consumption in modifying the risk of breast cancer was not investigated. Our findings in this study are, however, consistent with those in several reports indicating potential differences in the effects of GSTM1A and GSTM1B in breast and other cancers (Fryer et al, 1993a, b;Duncan et al, 1995;Inskip et al, 1995;Charrier et al, 1999). There is also the possibility that GSTM1 may be linked to another gene involved in the metabolism of putative breast carcinogens.…”
Section: Discussioncontrasting
confidence: 46%
“…Mais especificamente em relação ao carcinoma mamário, os resultados são inconsistentes e heterogêneos 8,[11][12][13][14][15] . Chacko et al (2005), em estudo caso-controle com 224 mulheres indianas, não observaram associação entre deleção do GSTM1 e aumento significativo no risco de câncer de mama.…”
Section: Discussionunclassified
“…Estudos epidemiológicos sugerem que indivíduos com deleção homozigótica do GSTM1 e do GSTT1 apresentam risco elevado de desenvolver vários tipos de neoplasia, incluindo câncer de bexiga, cólon, pulmão, pele e estômago 9 . No entanto, ainda não está estabelecida a associação entre genótipos GSTM1 e GSTT1 e risco de desenvolvimento de carcinoma mamário 8,[11][12][13][14][15] .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Helzlsouer et al [14] and Charrier et al [24] reported positive associations for the GSTM1 null genotype and post-menopausal women, whereas Ambrosone et al [20] reported a positive association between null GSTM1 and younger pre-menopausal women. Helzlsouer et al [14] reported no association for GSTT1 null genotype and breast cancer in pre-or post-menopausal women, whereas GarciaClosas et al [22] observed an inverse association for GSTT1 null genotype among pre-menopausal women.…”
Section: Discussionmentioning
confidence: 99%